Biogenic Synthesis of Gold Nanoparticles from Physalis peruviana and Application in Wound Healing - Stephen Adongo Odongo; Fredrick Oluoch Okumu; Solomon Omwoma Lugasi; Martin Opiyo Onani; Stephen Gaya Agong (Journal of Chemistry)
Wound management is key to healing. Poorly managed wounds lead to abnormal biological reactions and complications. Microorganisms, bacteria or fungi, infect such wounds leading to their chronic nature. Gold nanoparticles (Au NPs) show wound healing properties. In addition, ethnobotanical information from Siaya County in Kenya shows the leaves of Physalis peruviana L. to be effective in wound management. A combination of Au NPs and leave extracts of Physalis peruviana L. through a one pot biogenic synthesis leads to a new effective wound management substance. The synthesis was done at room temperature 25°C and at 85°C. The UV-visible spectroscopy results show efficient sharper plasmon bands with a blue shift indicating a decrease in λ max compared to red shift which show an increase in λ max. The surface plasmon resonance is a sharper at wavelength of about 540 nm. Dynamic light scattering and zeta potential analysis show that the polydispersity index is high and this is attributed to heterogeneity of chemical components of the plants. Transmission electron microscopy results for Au NPs show similarity in their shapes and sizes with grain size boundaries of between 1 nm and 100 nm. The particles are spherically shaped and crystalline with small lattice due to the small grains. The gold nanoparticles synthesized from Physalis peruviana show antimicrobial activities against gram-positive bacteria and, gram-negative bacteria as well as gram-positive fungus. The inhibition zones for Au NPs of different concentrations vary significantly between concentrations (one-way ANOVA at P<0.05). The highest antibacterial activity is at 100 mM of Au NPs against Escherichia coli, Bacillus subtilis, and Staphylococcus aureus. The inhibition zones for Au NPs at concentration of 100 mM and Physalis peruviana extract vary significantly in all the microbial cells, except for Pseudomonas aeruginosa (one-way ANOVA, F(3,11) = 2.67, P=0.1189). Application of the Au NPs in wound healing is faster than controls. The Au NPs also have good biocompatibility as signs of infection were not present.